2011
DOI: 10.1039/c1em10628g
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of occupational respirable crystalline silica exposure for quantitative exposure assessment in community-based case-control studies

Abstract: We describe an empirical model for exposure to respirable crystalline silica (RCS) to create a quantitative job-exposure matrix (JEM) for community-based studies. Personal measurements of exposure to RCS from Europe and Canada were obtained for exposure modelling. A mixed-effects model was elaborated, with region/country and job titles as random effect terms. The fixed effect terms included year of measurement, measurement strategy (representative or worst-case), sampling duration (minutes) and a priori exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 37 publications
13
46
0
Order By: Relevance
“…12 Also, multiple national and industry exposure databases from several European countries and Canada were recently used in conjunction with a literature review to empirically model occupational exposure to RCS, resulting in a quantitative job-exposure matrix. 13 We confirmed that construction and manufacturing of non-metallic minerals, which are sectors that are traditionally considered to expose workers to elevated levels of RCS, had the highest number of reported exposures. Mean air RCS concentration measured in these sectors (GM50.045 and GM50.017, respectively) are in line with concentrations reported in recent years in other European countries and in North America.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…12 Also, multiple national and industry exposure databases from several European countries and Canada were recently used in conjunction with a literature review to empirically model occupational exposure to RCS, resulting in a quantitative job-exposure matrix. 13 We confirmed that construction and manufacturing of non-metallic minerals, which are sectors that are traditionally considered to expose workers to elevated levels of RCS, had the highest number of reported exposures. Mean air RCS concentration measured in these sectors (GM50.045 and GM50.017, respectively) are in line with concentrations reported in recent years in other European countries and in North America.…”
Section: Discussionsupporting
confidence: 66%
“…[18][19][20] However, the subgroup of workers best characterized in our study, including those engaged in stonework masonry and tunnel construction, can reasonably be considered at high risk for adverse health effects as a result of silica exposure based on their higher mean exposure level (AM50.057, 93% of exposure measurements above the ACGIH limit value). 12,13,18,21 It should also be noted that carpenters and joiners had significant mean RCS exposure levels (AM50.047, 93% of exposure measurements above the ACGIH limit value), comparable with those of miners and quarry workers (AM50.048, 97% of exposure measurements above the ACGIH limit value), likely reflecting an inadequate implementation of preventive measures to control workplace silica dust air concentrations in the Italian construction industry, similar to other economically developed countries. [19][20][21] We estimate that about 30 000 workers are exposed to crystalline silica in the manufacture of non-metallic minerals in Italy (NACE code 26) 12 Similarly, in our study, exposure levels in the manufacture of nonmetallic minerals were found to vary between and within occupations, leading to an overall mean concentration lower than in construction, as well as a smaller percentage of TLV overwhelming values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peters et al 13 collated an immense database with the results of almost 360 000 measurements of five major lung carcinogens across multiple countries and industries. Modelling of part of this database has thus far resulted in a quantitative country-, job- and time period-specific exposure matrix for exposure to crystalline silica 14. Application of this exposure matrix to the almost 38 000 cases and controls resulted in a quantitative monotonic increasing exposure response curve for exposure to respirable crystalline silica and lung cancer risk, which appeared to be comparable with what had been reported within industry-based cohort studies 15.…”
supporting
confidence: 63%
“…1-3 However, to allow more precise risk estimation and extrapolation to lower levels of exposure, quantitative exposure assessment has become more common in retrospective studies in the form of expert assessment and/or statistical modeling of routinely collected measurement data. [4][5][6] Previous epidemiological investigations of benzene and health effects have relied on a variety of approaches for exposure assessment: (i) qualitative assessment, 7 (ii) semi-quantitative assessment sometimes augmented with some measurement data, 8 and (iii) quantitative assessment based on expert judgment and historical exposure measurements. 9 Vlaanderen et al 10,11 recently showed a relation between the quality of benzene exposure assessment and the ability to detect risk of hematolymphopoietic disorders thereby underlining the importance for high-quality exposure assessment in benzene health research.…”
Section: Introductionmentioning
confidence: 99%